Openness, Intermediate Imports and Growth - Andreas Kopp (Kiel Institute of World Economics (IfW), 2000)
We consider two channels via which foreign inputs into industrial production may lead to productivity effects. The first one concerns dynamic externalities between firms which share technical and organizational knowledge which is vital for the productivity growth of a particular industry. We show by which institutional mechanism firms are able to share proprietary knowledge which is of economic value for the competitor. An increase of the number of cooperating firms due to foreign direct investments leads to growth effects. The second channel of growth effects resulting from openness is derived from an increase of the imports of physical inputs due to a greater variety of inputs for final goods production.
Keywords: O19; O31; F23; F21; F12; 330; North-South trade; FDI; intermediate goods; Entwicklung; Politik der offenen Tür; Exportinduziertes Wachstum; Direktinvestition; Technologietransfer; Vorprodukt; Wissenstransfer; Business Network; Spillover-Effekt; Agglomerationseffekt; Urbanisierung; Nord-Süd-Beziehungen